2019
DOI: 10.18632/aging.102238
|View full text |Cite
|
Sign up to set email alerts
|

Telomere length, vitamin B12 and mortality in persons undergoing coronary angiography: the Ludwigshafen risk and cardiovascular health study

Abstract: Background: Vitamin B12 (B12) deficiency and excess are associated with increased risk of age-related-diseases and mortality. It has been suggested that high- and low-B12 concentrations link to increased mortality through accelerated genomic aging and inflammation. Evidence to support this is limited.Results: B12 was associated with all-cause-mortality, RTL and hsCRP in a non-linear fashion. The association between B12 and mortality was not independent, as it lost significance after adjustment for potential co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
(98 reference statements)
0
12
1
1
Order By: Relevance
“…A review by Rafnsson concluded that there was limited evidence that vitamin B12 deficiency predisposes to the risk of mortality and morbidity from either cardiovascular diseases or diabetes in adults [32]. Data from the LURIC study, however, showed a similar U-shaped curve for the association between serum B12 and mortality as in the present study [33]. These authors proposed that in low serum B12, mortality-and the accompanying accelerated telomere shortening-might be driven by increased concentrations of homocysteine, while in participants with high serum B12, this might be related to increased inflammation.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…A review by Rafnsson concluded that there was limited evidence that vitamin B12 deficiency predisposes to the risk of mortality and morbidity from either cardiovascular diseases or diabetes in adults [32]. Data from the LURIC study, however, showed a similar U-shaped curve for the association between serum B12 and mortality as in the present study [33]. These authors proposed that in low serum B12, mortality-and the accompanying accelerated telomere shortening-might be driven by increased concentrations of homocysteine, while in participants with high serum B12, this might be related to increased inflammation.…”
Section: Discussioncontrasting
confidence: 54%
“…We clearly showed that the use of vitamin B12-containing supplements has increased during the more recent NHANES surveys and was significantly higher in participants with hypertension, dyslipidemia, CVD, and an earlier diagnosis of cancer. The association between elevated serum B12 and cardiovascular mortality, together with the absence of any association between high B12 supplement intake and mortality likely indicates “reverse causality.” The increased use of vitamin B12-containing supplements by people with a chronic (cardiovascular) condition supports this conclusion, as well as the growing body of literature that serum B12 concentrations increase in states of inflammation [ 33 ]. However, there are several other factors which by themselves may negatively influence long-term morbidity and mortality, and are associated with higher serum B12 concentrations, for instance, high consumption of red meat.…”
Section: Discussionmentioning
confidence: 79%
“…Until now, the relationship between LTL and B12 has not been studied comprehensively, and the few existing data are inconsistent [ 63 , 96 , 97 ]. In the LURIC study [ 108 ], B12 was associated with all-cause-mortality, LTL and high sensitive C-reactive protein (hsCRP) in a non-linear fashion [ 108 ].…”
Section: B-vitamins Homocysteine Telomere Length and Cvdmentioning
confidence: 99%
“…Also, nutritional factors can modulate telomere length [41][42][43]. In particular, a sufficient supply with micronutrients like vitamin A, D, C, E, B12, folate, and nicotinamide is positively associated with telomere length [44][45][46][47][48]. Minerals like magnesium, zinc, and iron, and other dietary components, such as omega-3 fatty acid, polyphenols, and curcumin, are additional modulators of telomere length.…”
Section: Influencing Factors Of Telomere Lengthmentioning
confidence: 99%